Scaling Success Rates of Autonomous Coding Agents with File Dependency Complexity in SWE-Bench - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: How does the success rate of autonomous coding agents scale with the number of dependent file modifications in the SWE-bench evaluation framework. 11 claims were extracted from source literature; 8 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 7.2/10. This report is a machine-generated literature synthesis and does
Machine-generated literature synthesis.